An assessment of serum acid and alkaline phosphatase determinations in prostatic cancer with a clinical validation of an acid phosphatase assay utilizing adenosine 3′ -monophosphate as substrate. Issue 2 (February 1974) - Goldberg, David M.; Ellis, Graham
Abstract : Serum acid phosphatase (AcPase) was measured by a colorimetric method utilizing adenosine 3′ -monophosphate as substrate in 389 patients. In about half the cases blood was taken shortly after a rectal examination. The upper reference limit (mean + 2SD) for 116 cases with miscellaneous illness after eliminating outliers was 4·1 International Units per litre (U/I) at 37°C, and no correlation existed between AcPase activity and age in these subjects (r = 0·040). Eight of 18 patients with untreated carcinoma confined within the prostate gland had AcPase activities below 4·1 U/l, and all of 27 cases with extension to pelvic soft tissues or to bone exceeded this value. AcPase activities above 4·1 U/l were found in 6% of cases with benign hypertrophy of the prostate, in 5% of cases with non-prostatic cancer, and in none of 22 cases with other urological illness. Raised serum alkaline phosphatase (APase) activity was found in 60% of patients with untreated prostatic cancer and in only 6% of patients free of prostatic cancer, in most of whom there was a clinical explanation for the elevation. The correlation between the two phosphatase activities was not significant (r = 0·294). While APase activity does not reflect the stage of the disease as closely as AcPase activity, and is not so frequently elevated, it provided useful confirmation of the diagnosis in five patients of the present series whose AcPase levels were normal or only minimally elevated.